By how much could screening by primary human papillomavirus testing reduce cervical cancer incidence in England? - Castanon, Alejandra (J Med Screen, 2016)
OBJECTIVE: The replacement of cytology with human papillomavirus testing as the primary cervical screening test in England is imminent. In light of newly available evidence, we revised our previous estimates of the likely impact of primary human papillomavirus testing on incidence of cervical cancer. METHOD AND RESULTS: Using screening data on women aged 25–64 diagnosed with cervical cancer in England between 1988 and 2012, we previously reported that 38.8% had a negative test six months to six years prior to diagnosis. However, not all of these cancers would be prevented by human papillomavirus testing: for 1.0% the human papillomavirus positive test would come too late (within 18 months of diagnosis) to make a difference; 7.6% will have a negative human papillomavirus test (based on 79.9% sensitivity of human papillomavirus testing in cytology negative women); and 2.0% will develop cancer despite a positive human papillomavirus test. Additionally, we estimate that some women (equivalent to 4.3% of current incidence) whose cancers are currently prevented by cytology-based screening will have a false-negative human papillomavirus test. CONCLUSION: Overall, we estimate that 23.9% (95% CI: 19.3–27.6%) of current cases in women invited for screening could be prevented. Based on 2013 cancer incidence statistics, absolute numbers could be reduced by 487 (95% CI 394 to 563) or 3.4 (95% CI 2.8 to 4.0) per 100,000 women per year.